2006
DOI: 10.1287/mnsc.1060.0583
|View full text |Cite
|
Sign up to set email alerts
|

Information System Success: Individual and Organizational Determinants

Abstract: Despite considerable empirical research, results on the relationships among constructs related to information system (IS) success, as well as the determinants of IS success, are often inconsistent. A comprehensive understanding of IS success thus remains elusive. In an attempt to address this situation, which may partly be due to the exclusion of potentially important constructs from prior parsimonious models of IS success, we present and test a comprehensive theoretical model. This model explains interrelatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
353
3
25

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(407 citation statements)
references
References 60 publications
26
353
3
25
Order By: Relevance
“…These results are coherent with the studies which put forward logistics information perceived quality as LIS use determinant criteria (Igbaria, Zinatelli, Cragg & Cavaye, 1997;Michel & Cocula, 2014;Petter et al, 2013;Sabherwal, Jeyaraj & Chowa, 2006). Therefore, to improve LIS use level, the managers can adopt LIQ improvement policy on the basis of the found indicators.…”
Section: Discussionsupporting
confidence: 85%
“…These results are coherent with the studies which put forward logistics information perceived quality as LIS use determinant criteria (Igbaria, Zinatelli, Cragg & Cavaye, 1997;Michel & Cocula, 2014;Petter et al, 2013;Sabherwal, Jeyaraj & Chowa, 2006). Therefore, to improve LIS use level, the managers can adopt LIQ improvement policy on the basis of the found indicators.…”
Section: Discussionsupporting
confidence: 85%
“…Theory of planned behavior (Azjen, 1991) asserts that attitude is a direct determinant of behavioral intention, which in turns affects behavior. The case is also consistent with Sabherwal et al (2006) who found a positive relationship between attitude and behavioural use.…”
Section: Attitudesupporting
confidence: 89%
“…The user attitude is confirmed by the first agency and users who do not like to use the system will talk to their manager about their opinion and find ways not to use it. Fishbein and Azjen (1975) view attitude as the affect that one feels against or for some object or behavior (Sabherwal et al, 2006). Theory of planned behavior (Azjen, 1991) asserts that attitude is a direct determinant of behavioral intention, which in turns affects behavior.…”
Section: Attitudementioning
confidence: 99%
“…The same technique was employed to test factorial validity, resulting in fit statistics that again exceeded their recommended thresholds. In terms of nomological validity, all constructs in the model were based on those already used in the IS literature and adopted by several previous studies (Bhattacherjee & Premkumar, 2004;Juhani, 2005;Sabherwal et al, 2006;Agourram & Ingham, 2007;Petter et al, 2008). The proposed hypotheses had likewise previously been tested in IS research, and even the emerging relationship between Awareness of Others and system success had been partially tested, as a dimension of the Anonymity construct tested in the context of IS success (Pinsonneault & Heppel, 1998).…”
Section: Construct Validitymentioning
confidence: 99%